TEACHING TRANSLATION USING POETRY AT THE COLLEGE LEVEL IN UNIVERSITAS GRESIK - HIDAYAH NOR; IKA TRISNANTASARI (Fakultas Sastra Universitas Gresik, 2016)
This research describes how to teach translation using English poetry and applaying on the translation process by ESL college level students. It analyzes and codes the characteristics of their writing as well as the experiences and information reported in their reflective essays about the translation process. Poetry translation is discussed to honor the origin languange and corresponding culture and as a way to facilitate writing skill development for college students. The final project makes recommendations for future poetry translation assignments for college level with different topic and sources.